PENGARUH CURRENT RATIO, RETURN ON EQUITY DAN DEBT TO ASSET RATIO TERHADAP PRICE BOOK VALUE PERUSAHAAN ADVERTISING, PRINTING DAN MEDIA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2017 - Batin, Bayu Nur; Ismanto, Deny (Jurnal Fokus Manajemen Bisnis, 2019)
This  research was conducted with the aim of partially  testing  the influence of Current Ratio, Return On Equity, and Debt to Asset Ratio on Price Book Value to Advertising, Printing and Media companies listed on the Indonesia Stock  Exchange  (IDX).  Factors  that  influence  price  book  value  (PBV)  include liquidity that is proxied by current ratio or current ratio (CR), profitability projected with return on equity (ROE), and Debt to asset ratio (DAR). The research period was  carried out for 4 (four)  years,  namely  2014-2017. This  type  of  research  is Quantitative data, namely data in the form of numbers, or Quantitative data that are sent in a queue. The population in this study is a company engaged in the services of Advertising,  Printing, and Media services listed on the IDX, namely 15 companies. The sample in this study was obtained by purposive sampling method. Based on existing criteria, 15 companies were obtained. Hypothesis testing is done by Multiple  regression  analysis,  but  before testing  hypotheses  first  testing  the classical assumptions.  The results of hypothesis testing are carried out partially, namely the t test shows that CR has no effect and is not significant on PBV. ROE has a partial and significant effect on PBV. DAR partially has no effect and is  not significant for PBV.